Herpes zoster vaccine live: A 10 year review of post-marketing safety experience. Issue 52 (19th December 2017) - Willis, English D.; Woodward, Meredith; Brown, Elizabeth; Popmihajlov, Zoran; Saddier, Patricia; Annunziato, Paula W.; Halsey, Neal A.; Gershon, Anne A.
Highlights: After 10 years of post-marketing use, safety of zoster vaccine live remains favorable. 93% of reports of adverse experiences were non-serious. Injection-site reactions were the most commonly reported adverse experience. Vaccine-strain varicella-zoster virus was identified by PCR in 14 specimens. Disseminated herpes zoster was reported very rarely. Abstract: Background: Zoster vaccine is a single dose live, attenuated vaccine (ZVL) indicated for individuals ≥50 years-old for the prevention of herpes zoster (HZ). Safety data from clinical trials and post-licensure studies provided reassurance that ZVL is generally safe and well tolerated. The objective of this review was to provide worldwide post-marketing safety information following 10 years of use and >34 million doses distributed. Methods: All post-marketing adverse experience (AE) reports received worldwide between 02-May-2006 and 01-May-2016 from healthcare professionals following vaccination with ZVL and submitted to the MSD AE global safety database, were analyzed. Results: A total of 23, 556 AE reports, 93% non-serious, were reported. Local injection site reactions (ISRs), with a median time-to-onset of 2 days, were the most frequently reported AEs followed by HZ. The majority of HZ reports were reported within 2 weeks of vaccination and considered, based on time-to-onset, pathogenesis of HZ, and data from clinical trials, to be caused by wild-type varicella-zoster virus (VZV). HZ confirmed by PCR analysis to be VZV Oka/Merck vaccine-strain was identified in an immunocompetent individual 8 months postvaccination and in 4 immunocompromised individuals. Disseminated HZ was reported very rarely (<1%) with 38% occurring in immunocompromised individuals. All reports of disseminated HZ confirmed by PCR as VZV Oka/Merck vaccine-strain were in individuals with immunosuppressive conditions and/or therapy at the time of vaccination. Conclusions: The safety profile of ZVL, following 10 years of post-marketing use, was favorable and consistent with that observed in clinical trials and post-licensure studies.